(untitled) (Baghdad Science Journal, 2004)
The performance of single and two stage solar concentrator were studied ’ " The ratio of the primary to the secondary mirrors diameter is taking to be 0.5, depending on the theoretical calculation for the accumulated energy by the concentrator with ratio between 0.0 to 0.9. The design of the systems were designed and examined by using a ray-tracing program. The efficiency of the single and the two stage concentrators are calculated and compared with and without cooling systems.